Experimental investigation of free convection of glycol-Al2O3 nanofluid from horizontal tube - Cieśliński, Janusz T.; Smoleń, Sławomir; Sawicka, Dorota (Advances in Mechanical and Materials Engineering, 2017)
Nanofluids are considered to be a new generation of coolants, both in single- and two phase systems. Furthermore, nanofluids or nanocomposites may be used as a media in thermal energy storage (TES) in such systems as sensible heat storage (SHS) and phase change materials (PCM). In the SHS systems the dominating mechanism of the heat transfer is natural convection. However, in the literature only a few investigations of free convection of nanofluids have been discussed. This paper presents preliminary results of the experimental investigation of natural convection heat transfer of glycol-Al2O3 nanofluid from horizontal tube.